ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN TIMOR TENGAH UTARA - Ferdinandus Baptista Kosat (Ekopem: Jurnal Ekonomi Pembangunan, 2020)
ABSTRACT Economic development is interpreted as an effort to reduce poverty, tackling income inequality and providing employment. One of the most important indicators describing the success of economic development is the improvement of the quality of human resources. One of the benchmarks used in looking at the quality of human life is the health and economic index (purchasing power). The government as the implementer of development certainly needs quality human capital as the basic capital of development and produces quality people in North Central Timor Regency. The analysis method used is to use path analysis (path analysis) data in this study using secondary data collected in the form of time series data. The results of this study indicate that the Economic Growth variable (X1) has no significant effect on the Human Development Index (Y) variable with a significance value of 0.963> 0.05, then the Unemployment variable (X2) has no significant effect on the Human Development Index variable (Y ) with a significance value of 0.890> 0.05 and the poverty variable (X3) has a significant effect on the Human Development Index variable (Y) with a significance value of 0.001 <0.05. The results of this study indicate that the Poverty variable has a partial effect on the Human Development Index.